2009
DOI: 10.1111/j.1939-1676.2008.0255.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Risk Indicators in Canine Non‐Hodgkin's Lymphomas: Breed Associations and Geographic Distribution of 608 Cases Diagnosed throughout France over 1 Year

Abstract: Background: The etiology of non-Hodgkin's lymphomas (NHL) is multifactorial. Environmental and genetic factors are frequently incriminated both in humans and dogs.Objectives: Our purpose was to study the geographic distribution of canine NHL (CNHL) in France and to evaluate genetic and environmental influences.Animals: Six hundred and eight cases of CNHL, diagnosed throughout France over 1 year, were collected from 7 Veterinary Histopathologic Laboratories.Methods: Retrospective study. Breeds affected by lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0
20

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(136 citation statements)
references
References 41 publications
10
106
0
20
Order By: Relevance
“…Pastor et al (2009) and Ponce et al (2010) documented a significant overrepresentation of Boxers with T-cell lymphomas; however, the Boxer in this study had a B-cell lymphoma. Pastor et al (2009) also reported that German Shepherds and Rottweilers are predisposed to B-cell lymphomas; our results seem to support this observation, as all dogs of these breeds had the B-cell phenotype.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…Pastor et al (2009) and Ponce et al (2010) documented a significant overrepresentation of Boxers with T-cell lymphomas; however, the Boxer in this study had a B-cell lymphoma. Pastor et al (2009) also reported that German Shepherds and Rottweilers are predisposed to B-cell lymphomas; our results seem to support this observation, as all dogs of these breeds had the B-cell phenotype.…”
Section: Resultsmentioning
confidence: 46%
“…Some small breeds that frequently experience lymphoma include the Poodle and Scottish Terrier (MacEwen et al 1987, Dobson et al 2001, which were represented in this study. However, excluding the mixed breed animals, 59% of the dogs in this study were large breed, including the most frequently diagnosed Boxer, Rottweiler and German Shepherd (Dobson et al 2001, Pastor et al 2009). Pastor et al (2009) and Ponce et al (2010) documented a significant overrepresentation of Boxers with T-cell lymphomas; however, the Boxer in this study had a B-cell lymphoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed differences may be the result of the small number of dogs examined, or the fact that most of the dogs included in the study could be predisposed to B cell lymphoma development. Recent epidemiological research conducted on dogs from France indicated a clear predisposition of boxer dogs for T cell lymphoma development and German shepherd and rottweiler for B cell lymphomas (Pastor et al 2009). Although the present study does not include the epidemiological aspect, it at least partially supports the French authors observation, since in all boxers examined only T cell lymphomas were recognized (4 cases -33.3% of all T cell lymphomas) and in all German shepherds (3 cases -7.1% of all B cell lymphomas) only B cell lymphomas were recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Esta neoplasia se presenta en caninos, comúnmente entre los 6 a 12 años de edad, sin diferencias entre sexos 1,4,5 , siendo la alteración linfoproliferativa de mayor incidencia en pequeños animales 6 .…”
Section: Introductionunclassified